PENGARUH PROSEDUR PEMBAYARAN BIAYA RAWAT JALAN UMUM TERHADAP KEPUASAN PELANGGAN PADA RUMAH SAKIT SWASTA X DI KOTA BANDUNG - Reni Tawati; Eki Dudi Darmawan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
As the number of patients at hospital x in the city of Bandung increases, it will automatically increase the number of people who will queue during the payment process. Therefore, the general outpatient payment procedure is very important. Considering that patients who are not well have to queue for a long time to take a prescription or pay for the services of a doctor. Good and efficient procedures must fix this. In order to create queues that are not too long and patients can make payment transactions faster. So that patients will be more satisfied with the services of the procedures that have been made. If the patient is satisfied, and the patient is sick again, then the patient is likely to return for treatment at hospital x in the city of Bandung. Good procedures in the system, whether hospital systems or company systems, will make the business flow or process flow easier, also reduce operational costs and improve service quality. The results of the study obtained that 90% of patient satisfaction could be explained by the outpatient fee payment procedure variable and 10% was influenced by variables that were not examined by the researcher